PENGEMBANGAN E-BOOK IPAS BERBANTUAN CANVA UNTUK MENINGKATKAN HOTS PESERTA DIDIK KELAS V SD - Septia AP, Maisa; Fitria, Yanti; Helsa, Yullys; Zuryanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology requires learning processes that foster students’ Higher Order Thinking Skills (HOTS). However, based on observations conducted in several elementary schools, science and social studies (IPAS) learning is still dominated by the use of conventional textbooks that lack interactivity, resulting in limited opportunities for students to develop HOTS. In addition, previous studies on Canva-assisted E-Books have primarily focused on improving learning outcomes and learning motivation, while research specifically developing E-Books to enhance HOTS in elementary school IPAS learning remains limited. Therefore, this study aimed to develop a Canva-assisted IPAS E-Book on the topic “My Beloved Earth, My Damaged Earth” that is valid, practical, and effective in improving the HOTS of fifth-grade elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were fifth-grade students from SDN 01 Bandar Buat, SDN 10 Bandar Buat, and SDN 21 Bandar Buat. The research instruments included validation sheets, teacher and student response questionnaires, and pretest-posttest tests. The results showed that the validity level of the developed E-Book reached 86.19% (very valid), the practicality level reached 89.33% based on teacher responses and 93.58% based on student responses (very practical), and the effectiveness level obtained an average N-Gain score of 73.68% (effective). Therefore, the Canva-assisted IPAS E-Book developed in this study is considered feasible, practical, and effective in improving students’ Higher Order Thinking Skills in IPAS learning.